Renal-type clear cell carcinoma of prostate: A case report and review of literature - Guangjie Liao; Xinke Zhang; Zhongjian Li; Su Lan; Miaoli Huang; Weijian Huang (Wolters Kluwer Medknow Publications, 2018)
We analyzed the clinicopathological features of renal-type clear cell carcinoma (RTCCC) in the prostate and its diagnosis according to the example in our hospital and review of the literature. Clinicopathological features of RTCCC in the prostate were observed in a patient from our hospital combining with a review of the literature. Microscopically, the tumor was composed of cells with abundant and translucent cytoplasm, arranged in the form of the vesicular nest or glandular structure. Therefore, it was necessary to distinguish between metastatic clear cell renal cell carcinoma and primary RTCCC in the prostate. Immunohistochemistry (IHC) of this case showed tumor cells were positive expression for cytokeratin (CKpan), low-molecular weight cytokeratin, epithelial membrane antigen, and prostate-specific antigen (PSA), P504S, prostate-specific membrane antigen and partial positive expression for vimentin and CD10. The tumor cells displayed negative expression of high molecular weight cytokeratin, cytokeratin 7 (CK7), CK34, PAX8, and renal cell carcinoma. The morphological and immunohistochemical features of this tumor were in correspondence with RTCCC of the prostate. This tumor is a rare variant of the prostate carcinomas. To the best of our knowledge, this type of extrarenal tumor has only been reported in six previous studies. Combination of histology, IHC, imaging, and serum PSA is needed to perform a suitable diagnosis.